Perbedaan Kemandirian Anak Usia Dini Berdasarkan Status Pekerjaan Ibu Di MDA Kampung Durian Kecamatan Medan Perjuangan - Mayasari Mayasari; Muhammad Takwin Machmud; Yusnadi Yusnadi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This study aims to determine differences in early childhood independence based on the mother's employment status in MDA Kampung Durian, Medan Perjuangan District. The method used in this study is a qualitative method using descriptive qualitative data analysis, namely data collected in the form of words, pictures and not numbers. The data used in this research is primary data. Namely data obtained directly from the field. In this study, primary data was obtained by observation and interviews. The results of this study are that children whose mothers work have a high level of independence compared to children whose mothers do not work and the status of mothers who work or not can also be a factor of a child's independence.